Analisis Penerapan PSAK 407 tentang Akuntansi Ijarah pada Pembiayaan Perbankan Syariah di Bank BJB Syariah KC Bandung Pelajar Pejuang - Deska Pratama; Mia Lasmi Wardiyah (PT. Saha Kreasi Indonesia, 2025)
This study aims to analyze the application of Statement of Financial Accounting Standards (PSAK) 407 concerning Ijarah Accounting in Islamic banking financing at Bank BJB Syariah Bandung Branch Office Pelajar Pejuang. The research used a descriptive qualitative method with a case study approach, through interviews, observation, and documentation. The results showed that Bank BJB Syariah has implemented PSAK 407 in recording and reporting ijarah transactions, including recognition, measurement, presentation, and disclosure in accordance with sharia principles. However, there are still some obstacles in implementation, such as human resources' understanding of sharia accounting standards and accounting information system adjustments. These findings emphasize the importance of continuous training and periodic evaluation to improve compliance and consistency in the application of PSAK 407 on ijarah financing products. This research is expected to contribute to the development of transparent and accountable Islamic accounting practices in the Islamic banking sector.